1982
DOI: 10.1126/science.7041259
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Thymectomy Prevents Spontaneous Diabetes Mellitus in the BB/W Rat

Abstract: Complete neonatal thymectomy reduced the frequency of spontaneous diabetes mellitus in BioBreeding/Worcester rats from 27 to 3 percent. Incomplete thymectomy also significantly reduced the frequency of diabetes (to 9 percent). These findings strengthen the hypothesis that thymus-dependent, cell-mediated autoimmune destruction of pancreatic B cells is responsible for the pathogenesis of diabetes in this experimental animal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(102 citation statements)
references
References 13 publications
6
96
0
Order By: Relevance
“…For example, in the DP-BB rat model of diabetes, an early time interval has been identified in which diabetes can be prevented (1). Thymectomy of DP-BB rats around 30 days of age prevents IDDM, whereas thymectomy at day 60 has no effect (13). Accordingly, injection with regulatory RT6 þ T cells from DR-BB rats in the period from 21 to 60 days of age prevents diabetes in DP-BB rats, while injection from 60 to 100 days does not influence the disease (14).…”
Section: Introductionmentioning
confidence: 86%
“…For example, in the DP-BB rat model of diabetes, an early time interval has been identified in which diabetes can be prevented (1). Thymectomy of DP-BB rats around 30 days of age prevents IDDM, whereas thymectomy at day 60 has no effect (13). Accordingly, injection with regulatory RT6 þ T cells from DR-BB rats in the period from 21 to 60 days of age prevents diabetes in DP-BB rats, while injection from 60 to 100 days does not influence the disease (14).…”
Section: Introductionmentioning
confidence: 86%
“…Like et al [9] have also reported a similar effect of neonatal thymectomy on insulitis in BB/W rats that spontaneously develop insulin-dependent diabetes mellitus [13,15]. Neither paper explains why complete abolishment of insulitis was unsuccessful in thymectomized mice and rats.…”
mentioning
confidence: 82%
“…1 " 4 (2) modification and possible prevention of the syndrome by treatment with anti-lymphocyte serum; 5 (3) possible prevention by neonatal thymectomy 6 and by bone marrow transplantation from normal rats; 7 (4) the demonstration of passive transfer of insulitis by lymphocytes from dia-betic rats injected into nude mice; 8 and (5) the presence of lymphopenia before and after development of diabetes.…”
mentioning
confidence: 99%